2016
DOI: 10.1002/cssc.201501256
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and Interfacial Modification of Cu2ZnSn(S,Se)4 Thin‐Film Solar Cells Prepared by Electrochemical Deposition

Abstract: A highly efficient Cu2 ZnSn(S,Se)4 (CZTSSe)-based thin-film solar cell (9.9%) was prepared using an electrochemical deposition method followed by thermal annealing. The Cu-Zn-Sn alloy films was grown on a Mo-coated glass substrate using a one-pot electrochemical deposition process, and the metallic precursor films was annealed under a mixed atmosphere of S and Se to form CZTSSe thin films with bandgap energies ranging from 1.0 to 1.2 eV. The compositional modification of the S/(S+Se) ratio shows a trade-off ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…1720 Although a highest efficiency of ∼9.9% has been achieved for an electrodeposited CZTSSe TFSC, there are several issues associated with the electrodeposition of CZTS-based absorber layers. 21 Electrodeposition of stacked elemental layers often results in spatial compositional inhomogeneity in the absorber layer after sulfurization/selenization owing to the nonuniform deposition of Zn on the islandlike growth of Sn onto the Cu surface. 22,23 On the other hand, coelectroplating of the precursors shows a dendritic growth, which generally results in an uneven surface microstructure with spatial distribution of micron-sized grains after sulfurization/selenization.…”
Section: Introductionmentioning
confidence: 99%
“…1720 Although a highest efficiency of ∼9.9% has been achieved for an electrodeposited CZTSSe TFSC, there are several issues associated with the electrodeposition of CZTS-based absorber layers. 21 Electrodeposition of stacked elemental layers often results in spatial compositional inhomogeneity in the absorber layer after sulfurization/selenization owing to the nonuniform deposition of Zn on the islandlike growth of Sn onto the Cu surface. 22,23 On the other hand, coelectroplating of the precursors shows a dendritic growth, which generally results in an uneven surface microstructure with spatial distribution of micron-sized grains after sulfurization/selenization.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the efficiency of the best CZTSSe solar cells was significantly enhanced from 7.11% (reference CZTSSe device) to 9.40%, which is close to the highest reported efficiency of CZTSSe thin-film solar cells prepared by electrodeposition (i.e., 9.9%). 23 The rough CZTSSe thin-film solar cells with effectively reduced interfacial detrimental defects through the PHT process exhibited reduced charge recombination and improved photovoltaic performances like higher V OC and FF. film deposited by electrodeposition is known to be relatively high 5,25 compared with those deposited by other techniques such as sputtering, 26 spray method, 27 and thermal co-evaporation.…”
mentioning
confidence: 96%
“…Various methods have been used to prepare CZTSSe-based thinfilm solar cells, including sputtering, 2,7,[13][14][15] thermal evaporation, 16 electron-beam evaporation, 17 sol-gel methods, 18,19 spin coating, 20 spray pyrolysis, 21 electrochemical deposition, 5,22,23 and the hydrazine-slurry method. 6 However, these methods have shortcomings such as expensive precursors, time-consuming processes, complicated apparatus, and the use of toxic substances (e.g., hydrazine).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Watson, in 2013 obtained the best performances for CZTSSe based solar cells with power conversion efficiency equal to 12.6% [8,9]. Several research groups reported the growth and fabrication of CZTSSe solar cells using various methods such as sputtering followed sulfo-selenization [10,11], solution growth process [12,13], nano-particle approach [14,15], electrodeposition [16,17], ink jet printing [18], pulsed laser deposition [19,20], ball milling and hybrid ink followed by sulfoselenization [21,22].…”
Section: Introductionmentioning
confidence: 99%